(sinA+cosA)/(sinA-cosA)=3+2√2 求cosA
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/04 03:26:14
(sinA+cosA)/(sinA-cosA)=3+2√2求cosA(sinA+cosA)/(sinA-cosA)=3+2√2求cosA(sinA+cosA)/(sinA-cosA)=3+2√2求co
(sinA+cosA)/(sinA-cosA)=3+2√2 求cosA
(sinA+cosA)/(sinA-cosA)=3+2√2 求cosA
(sinA+cosA)/(sinA-cosA)=3+2√2 求cosA
同除以cosA
(tanA+1)/(tanA-1)=3+2√2
tanA=√2
即sinA/cosA=√2 sinA=√2cosA
∵(sinA)^2+(cosA)^2=1
∴(√2cosA)^2+(cosA)^2=1
解得cosA= ±√3 /3
-sina/-cos*-sina*cosa
sina>cosa,sina
sina-cosa
化简cosA+sinA/cosA-sinA
3sina=2cosa 则(cosa-sina/cosa+sina)+(cosa+sina/cosa-sina)=______
3sina=2cosa 则(cosa-sina/cosa+sina)+(cosa+sina/cosa-sina)=______
求证:1+sina+cosa/1+sina-cosa+1-cosa+sina/1+cosa+sina=2/sina
证明=[(sina+cosa)+(sina+cosa)²]/(1+sina+cosa) =(sina+cosa)(1+sina+cosa)/(1+sina+cosa)
化简(1/sina+cosa/sina)(1-cosa)
化简;sina+cosa:和sina -cosa
sina-cosa/cosa+sina等于多少!
矩阵(cosa -sina sina cosa)^n等于
sina+sina=1 求cosa+cosa
sina-cosa=m,求cosa+sina
化简(sina+2cosa)/(sina-cosa)=
化简tana(cosa-sina)+sina(sina+tana)/1+cosa
化简:sina^2/(sina-cosa)-(sina+cosa)/(tan^2-1)
Sina=2Cosa,则Sina^2+2Sina*Cosa